A novel MDSC-induced PD-1−PD-L1+ B-cell subset in breast tumor microenvironment possesses immuno-suppressive properties. (3rd April 2018) - Shen, Meng; Wang, Jian; Yu, Wenwen; Zhang, Chen; Liu, Min; Wang, Kaiyuan; Yang, Lili; Wei, Feng; Wang, Shizhen Emily; Sun, Qian; Ren, Xiubao
ABSTRACT: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous group of myeloid cells that suppress T-cell activity in a tumor microenvironment. However, the suppressive function of MDSCs on B cells and its underlying mechanism remain unclear. Here, we show that in 4T1 breast cancer mice, a significantly increased number of MDSCs, in parallel with splenic B cells, are accumulated when compared to normal mice. In the presence of MDSCs, the surface molecules of B cells are remolded, with checkpoint-related molecules such as PD-1 and PD-L1 changing prominently. MDSCs also emerge as vital regulators in B-cell immune functions such as proliferation, apoptosis and the abilities to secrete antibodies and cytokines. Our study further identifies that MDSCs can transform normal B cells to a subtype of immuno- regulatory B cells (Bregs) which inhibit T-cell response. Furthermore, we identified a novel kind of Bregs with a specific phenotype PD-1 − PD-L1 + CD19 +, which exert the greatest suppressive effects on T cells in comparison with the previously reported Bregs characterized as CD1d + CD5 + CD19 +, CD5 + CD19 + and Interleukin (IL)-10-secreting B cells. Our results highlight that MDSCs regulate B-cell response and may serve as a therapeutic approach in anti-tumor treatment. Investigation of this new Breg subtype extends our understanding of regulation of T-cell response and sheds new light on anti-tumor immunity and immune therapy.